Entrepreneurial Knowledge and Sustainable SMEs Performance: The Mediation Role of Strategic Opportunity Recognition - Lip, Teh Kean; Abd Wahab, Sazali; Yusoff, Tairuddin; Sohail, Nadia; Muthaya, Karthigesu; Abdulsamad, Akram; Al-refaei, Abd Al-Aziz (Advances in Social Sciences Research Journal, 2025)
From a sustainability standpoint, Small and Medium Enterprises (SMEs) stand to have the advantage of reduced costs and risks by integrating innovation into their networking and strategic activities. As such this study aims to construct a model to show the impact of entrepreneurial knowledge on the sustainable performance of SMEs. The model will also include the mediation effect of corporate spirituality on the proposed relationship. This paper reviewed various literature on strategic management and sustainable SME performance. This paper has recognised holistic models of sustainable SME performance to give a comprehensive view of the important impact of entrepreneurial knowledge on sustainable SME performance. This finding is useful for SMEs to establish a competitive advantage to enhance their performance. The flexibility of the newly developed concept allows it to be utilised in different situations, i.e., economic crisis or dramatic economic landscape changes, by employing sustainable entrepreneurship theory to mitigate the issues.